1997
DOI: 10.1021/bk-1997-0664.ch020
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Chromium from Water and Soil by Vascular Aquatic Plants

Abstract: The ability of aquatic plants to absorb, translocate and concentrate metals has led to the development of various plant-based treatment systems. The potential to accumulate chromium by Scirpus lacustris, Phragmites karka and Bacopa monnieri was assessed by subjecting them to different chromium concentrations under laboratory conditions. Plants showed the ability to accumulate substantial amounts of chromium during a short span of one week. When the plants were grown in tannery effluent and sludge containing 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 11 publications
0
38
0
2
Order By: Relevance
“…(Chandra et al, 1997), estimated that in India alone about 2600 to 4200 tonnes of elemental Cr escape into the environment annually from the tanning industries, with a Cr concentration ranging between 2000 and 5000 mg L−1 in the effluent compared to the recommended permissible limit of 2 mg L−1. Typical concentrations in natural soils are 1-1000 mg /kg soil (Cappuyns et al, 2002). In the present study chromium was found with the concentration of 6.6mg/kg to 246.0 mg/kg in wet season and 6.9 mg/kg to 256.0 mg/kg in dry season.…”
Section: Chromiummentioning
confidence: 99%
“…(Chandra et al, 1997), estimated that in India alone about 2600 to 4200 tonnes of elemental Cr escape into the environment annually from the tanning industries, with a Cr concentration ranging between 2000 and 5000 mg L−1 in the effluent compared to the recommended permissible limit of 2 mg L−1. Typical concentrations in natural soils are 1-1000 mg /kg soil (Cappuyns et al, 2002). In the present study chromium was found with the concentration of 6.6mg/kg to 246.0 mg/kg in wet season and 6.9 mg/kg to 256.0 mg/kg in dry season.…”
Section: Chromiummentioning
confidence: 99%
“…These are Ipomoea carnea, Dhatura innoxia, Cassia tora and Lantana camara (all are local weeds). Another example of a plant that has shown much promise in the treatment of metal pollutant is Phragmytes karka, it has the ability to take up chromium from contaminated water [10,22]. Though studies on Phragmytes karka were hydroponic, soil studies on chromium accumulation are scarce.…”
Section: Role Of Chromium In Plantsmentioning
confidence: 99%
“…In recent years, it has been used as a decorative plant, but its medicinal use has not been well established. Removal of heavy metals and pollutants from aquatic systems by H. umbellata has been studied 12,15 . In addition, Hydrocotyle spp.…”
Section: Introductionmentioning
confidence: 99%